2021
DOI: 10.1186/s12877-021-02600-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with mobility decrease leading to disability: a cross-sectional nationwide study in Japan, with results from 8681 adults aged 20-89 years

Abstract: Background Mobility decrease leading to disability can gradually develop during early life, however, its related factors are not well clarified. Therefore, we investigate the related factors of mobility decrease at various levels, using nationwide data in Japan. Methods In total, 8681 independent community dwellers aged 20-89 years were analysed (average age, 51.6 years; 58.5% women). Three stages of mobility decrease were based on the locomotive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…(4) In rapidly ageing countries such as Japan and China, the proportion of older adults aged 65 years and above with disability and requiring long-term care in Japan is around 20%, while the proportion of older adults with ADL disability in China was 18.3% in 2015. (5,6) Current evidence on functional disability prevalence is inconclusive as to whether disability rates are rising or declining. Although a decline in prevalence has been reported in some countries (7,8), population ageing can be expected to lead to increasing numbers of older adults with functional disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…(4) In rapidly ageing countries such as Japan and China, the proportion of older adults aged 65 years and above with disability and requiring long-term care in Japan is around 20%, while the proportion of older adults with ADL disability in China was 18.3% in 2015. (5,6) Current evidence on functional disability prevalence is inconclusive as to whether disability rates are rising or declining. Although a decline in prevalence has been reported in some countries (7,8), population ageing can be expected to lead to increasing numbers of older adults with functional disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…These factors causing mobility or immobility add up to a holistic understanding of mobility. Research on the range of factors influencing mobility and corresponding assessment tools has already been called for in the current literature in the field of mobility research ( 26 , 27 ). The results regarding contextual factors are discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…A study found that disability is associated with smoking, obesity, the female sex, and diabetes in predicting disability and death in the Australian population ( 19 ). A nationwide cross-national study that explored factors related to reduced mobility leading to disability in adults aged 20–89 years, found that an increase in the age of participants over 40 years was associated with a new decrease in mobility, and lifestyle habits of participants younger than 40 years, including reduced physical activity in women and being overweight, which were in turn, associated with reduced mobility at all levels ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many studies have identified that certain chronic diseases like hypertension, hyperlipidemia, joint, kidney and diseases [e.g., hypertension, ( 8 , 19 , 22 , 30 , 41 , 43 ) hyperlipidemia ( 19 ), diabetes, ( 8 , 30 , 35 , 36 , 40 , 41 , 51 , 55 , 57 ) cerebrovascular disease ( 18 , 30 , 51 ), respiratory and lung disease ( 15 , 30 , 43 , 45 , 50 , 57 ), cardiovascular disease ( 11 13 , 30 , 32 , 45 , 57 ), heart disease ( 35 , 41 , 46 , 51 ), hip joint disease ( 30 , 58 ), tuberculosis ( 54 ), kidney disease ( 44 ), HIV ( 14 ), cancer ( 30 , 41 , 57 ), and BMI/obesity ( 9 , 19 , 21 , 22 , 26 , 27 , 29 , 32 , 36 , 39 , 41 , 45 ), etc.] or health-related factors, behaviors and choices [e.g., level of physical activity ( 6 9 , 16 , 27 , 28 , 31 34 , 38 , 42 , 44 , 56 ), smoking ( 9 , 19 ,…”
Section: Introductionmentioning
confidence: 99%